TINJAUAN FAKTOR PENYEBAB TERJADINYA DUPLIKASI REKAM MEDIS GUNA MENUNJANG KUALITAS PELAYANAN DI BAGIAN FILLING RSUD BANDUNG KIWARI - Hada, Encep; Monica, Rizqy Dimas; Aliana, Feby Alin (Jurnal TEDC; Vol 17 No 3 (2023): JURNAL TEDC, 2023)
The results of a preliminary study at the Bandung Regional General Hospital Kiwari in the March – December 2022 Service found 78 duplicated medical records unsustainable medical record Data and inefficient resources are prone to duplication of medical records so that it can hinder the service process in the filling section. The purposeof this study is to determine the factors that cause duplication of medical records in order to support the quality of Service in the filling of hospitals in Bandung Kiwari.The research method used is a descriptive method with a qualitative approach. Data collection techniques with observation, literature studies and documentation. Instruments in the study using interview guidelines, recording equipment, stationery, Cheklist sheet.The results ofthe implementation of medical record storage using centralization and numbering of medical records using the unit system (unit numbering system) but for the implementation process is not good enough. Factors causing duplication of medical records in hospitals in Bandung Kiwari is the lack of communication between officers, limited inventory of medical records document folder and medical records of patients who were not found. The effort made by the hospital is to increase the accuracy of the officers through the training of checking back on the expedition SIMRS, and if the medical record is not found then a temporary file is made. It is recommended that communication be improved for coordination and improving the knowledge of employees whose qualifications are not suitable through formal and non-formal education.